Uso de álcool e tabaco entre universitários de fisioterapia de uma universidade pública - Moraes, Monique Rangel do Nascimento de (2021)
The prevalence of psychoactive substance use among college students is higher when compared to the general population. The objective of the present study was to analyze the factors associated with the use of alcohol and tobacco among physical therapy undergraduate students at a public university. This is a cross-sectional study, with a quantitative approach, developed in a sample of 154 university students, which corresponds to 60.6% of the students enrolled in the physical therapy course in the year 2018. The statistical analyses involved were the univariate, chi-square and Fisher's exact tests and binary logistic regression. There was a predominance of female gender (74.7%), with a mean age of 21.35 years, Catholic religion (50.0%), and social classes A/B (53.2%). The prevalence of alcohol use among physiotherapy students was higher when compared to the general population, with lifetime, year and month rates respectively of 80.5% and 68.1%; 61.2% and 46.4%; 60.4% and 33.0%. As for tobacco use, we observed that 39% of the students reported lifetime use, 22.1% yearly use, and 9.1% monthly use. When comparing these findings with the study done in the university population we noticed that tobacco use was lower in the sample studied, on the other hand, we observed that the frequency of lifetime use of this substance was higher among physiotherapy students compared to other courses studied by the Center for Studies and Research on Alcohol and Other Drugs: Interconnections. Associations were found in the frequencies of lifetime, year, and month use of alcohol that remained after the regression model, with students from earlier periods less likely to use this substance in their lifetime (OR: 2.53; IC95%: 1.074-5.965); in students from the white ethnic group less likely to use alcohol in the year (OR: 0.45; IC95%: 0.229-0.897) and month (OR: 0.44; IC95%: 0.224-0.867). In addition, students from the white ethnic group, belonging to social classes C/D/E, respectively, were less likely to binge drink in the past 12 months (OR: 2.13; IC95%: 1.093-4.154; OR: 2.14; IC95%: 1.098-4.182). As for lifetime tobacco use, the factors that remained associated were being female and having religion, respectively, being less likely to use this substance in their lives (OR: 0.46; IC95%: 0.219-0.997); (OR: 3.81; IC95%: 1.344-10.845). In addition, being female, non-white ethnic group, and being a practitioner of religion, respectively, were associated with less chance of making tobacco use in the year (OR: 0.27; IC95%: 0.115-0.656; OR: 0.39; IC95%: 0.171-0.931; OR: 3.51; IC95%: 1.385-8.900). The results show that there is a need to understand the consumption of these substances and the aspects related to quality of life in this population sample, since it will enable the creation of support mechanisms for coping with adversities and subsidies that can guide the development of strategies for health promotion and quality of life, as well as a policy of prevention of substance use to improve the health conditions of physical therapy students at the university level.